Financial Innovation and Market Transformation in the Age of Digital Finance - Zhou, Shijie (Transactions on Economics, Business and Management Research, 2024)
This manuscript scrutinizes the profound transformation digital financial innovations have induced within traditional financial landscapes, positing a trajectory for forthcoming advancements. It delineates the transition from conventional to digital finance, emphasizing the instrumental role played by blockchain, cryptocurrencies, fintech breakthroughs, and artificial intelligence in the reconfiguration of financial services. The discourse elaborates on the enhancements in efficiency, inclusivity, and interconnectedness fostered by digital finance, concurrently navigating through the intricacies and challenges it precipitates. By investigating the socio-economic repercussions, regulatory obstacles, cybersecurity threats, and concerns regarding market stability, the study furnishes insights into the reformation of market operations, regulatory architectures, and the prospective direction of the finance sector. Moreover, it probes into the advent of Central Bank Digital Currencies (CBDCs), the sustainability of fintech, decentralized finance (DeFi), and the extensive ramifications of these technologies on financial markets, economic systems, and social frameworks.